DROPOUT TENDENCIES IN TURKISH HIGHER EDUCATION - Serbes, Duygu Ilkdogan; Yildiz, Aydin Balyer (SCIENTIA SOCIALIS, 2025)
Dropping out of higher education is a significant issue that impacts not only individual students but also the educational system and society at large. The purpose of the study is to examine the levels of dropout tendency among undergraduate students attending public universities in T & uuml;rkiye and to determine whether these tendencies vary according to specific demographic variables. The sample included 1,061 students, of whom 58.2% (n = 617) were female and 41.8% (n = 444) male, enrolled in public universities in T & uuml;rkiye. Data were collected using the School Dropout Scale in Higher Education and a demographic information form. The findings indicated that students in their third year or above demonstrated higher dropout tendencies compared to those in earlier stages of their studies, including preparatory, first, and second-year students. Additionally, students studying in metropolitan cities (Ankara, Izmir, Istanbul) demonstrated significantly lower dropout tendencies than those in other cities. A decrease in school attendance was associated with a statistically significant rise in dropout tendency. Students who worked while studying were more likely to show dropout tendencies than those who did not work. Furthermore, higher parental educational levels correlated with a significant decrease in dropout tendency. Similarly, students with higher Grade Point Average (GPA) exhibited a lower tendency to drop out. Conversely, lower family income and a greater number of siblings were associated with a significant increase in dropout tendency. No statistically significant difference was found regarding gender.
Keywords: Tintos' dropout model; higher education; human capital; youth poverty; diploma inflation; descriptive correlational research; SCHOOL; MODEL; Education & Educational Research